In vitro Type II Restriction of Bacteriophage DNA With Modified Pyrimidines - Flodman, Kiersten; Corrêa, Ivan R.; Dai, Nan; Weigele, Peter; Xu, Shuang-yong (Frontiers in Microbiology, 2020)
To counteract host-encoded restriction systems, bacteriophages (phages) incorporate modified bases in their genomes. For example, phages carry in their genomes modified pyrimidines such as 5-hydroxymethyl-cytosine (5hmC) in T4gt deficient in - and -glucosyltranferases, glucosylated-5-hydroxymethylcytosine (5gmC) in T4, 5-methylcytosine (5mC) in Xp12, and 5-hydroxymethyldeoxyuridine (5hmdU) in SP8. In this work we sequenced phage Xp12 and SP8 genomes and examined Type II restriction of T4gt, T4, Xp12, and SP8 phage DNAs. T4gt, T4 and Xp12 genomes showed resistance to 81.9% (186 out of 227 enzymes tested), 94.3% (214 out of 227 enzymes tested), and 89.9% (196 out of 218 enzymes tested), respectively, commercially available Type II restriction endonucleases (REases). The SP8 genome, however, was resistant to only ~8.3% of these enzymes (17 out of 204 enzymes tested). SP8 DNA could be further modified by adenine DNA methyltransferases (MTases) such as M.Dam and M.EcoGII as well as a number of cytosine DNA MTases, such as CpG methylase. The 5hmdU base in SP8 DNA was phosphorylated by treatment with a 5hmdU DNA kinase to achieve ~20% phosphorylated 5hmdU, resulting resistance or partially resistant to more Type II restriction. This work provides a convenient reference for molecular biologists working with modified pyrimidines and using REases. The genomic sequences of phage Xp12 and SP8 lay the foundation for further studies on genetic pathways for 5mC and 5hmdU DNA base modifications and for comparative phage genomics.